Indications, types, and diagnostic implications of prenatal genetic testing in Sub-Saharan Africa: A descriptive study - Sium, Abraham Fessehaye; Shimels, Tariku; Abdosh, Abdulfetah Abdulkadir; Diress, Tesfaye; Tsegaye, Tigist; Yifrashewa, Tizibt; Terefework, Zewdu; Gudu, Wondimu (PloS one, 2023)
To describe indications, test types, and results of prenatal diagnostic genetic amniocentesis among Ethiopian pregnant women. This study was a descriptive study on prenatal diagnostic genetic testing among Ethiopian pregnant women with certain indications and it was conducted at St. Paul's Hospital Millennium Medical College (Addis Ababa, Ethiopia) from January 2017 to April 2023. Data on sociodemographic characteristics, genetic testing indications, types, and results were collected electronically. Data were analysed using SPSS version 23. A total of 159 cases were analysed. The commonest indication for genetic testing among the study subjects was major fetal structural anomalies identified on specialized prenatal anatomic scanning of the index pregnancy detected in 71(44.7%) cases. Down syndrome and Edward syndrome were the commonest genetic aberrations detected accounting for 6.3% (10/159) and 4.4% (7/159), respectively. Among the rare genetic aberration detected were Di-George syndrome (0.6%) and Duchenne muscular dystrophy (0.6%).